1
$\begingroup$

I have problems to solve this limit $$\lim _{x\to \infty }\left(x\sqrt{x^2-x}-x^2\cos\left(\frac{1}{\sqrt{x}}\right)\right)$$ I tried with Taylor: $$\lim _{x\to \infty }\left(x^2\sqrt{1-\frac{1}{x}}-x^2\left(1-\frac{1}{2x}+\frac{1}{24x^2}\right)\right)=\lim _{x\to \infty }\left(x^2-x^2+\frac{x}{2}-\frac{1}{24}\right)=\infty$$ that is the wrong result, in must be $\color{red}{-\frac{1}{6}}$

$\endgroup$
3
$\begingroup$

Hint: You need to use the Taylor series expansion for the square root as well as the cosine. Expanding $\sqrt{1-u}$ around $u=0$ we have that $$\sqrt{1-u}=1-\frac{u}{2}-\frac{u^2}{8}+O(u^3)$$ and so as $x\rightarrow \infty$ $$x^2\sqrt{1-\frac{1}{x}}=x^2-\frac{x}{2}-\frac{1}{8}+O\left(\frac{1}{x}\right).$$

$\endgroup$
1
$\begingroup$

Full solution:

$$\lim _{x\to \infty }\left(x\sqrt{x^2-x}-x^2\cos\left(\frac{1}{\sqrt{x}}\right)\right)= \lim _{x\to \infty }x^2\left(\sqrt{1-\frac{1}{x}}-\cos\left(\frac{1}{\sqrt{x}}\right)\right)=$$$$=\lim _{t\to 0}\frac{\sqrt{1-t^2}-\cos{t}}{t^4} =\lim _{t\to 0}\frac{1-t^2-\cos^2{t}}{t^4(\sqrt{1-t^2}+\cos{t})}=\frac{1}{2}\lim _{t\to 0}\frac{\sin^2t-t^2}{t^4}=$$$$=\frac{1}{2}\lim _{t\to 0}\frac{\sin t+t}{t}\cdot\lim _{t\to 0}\frac{\sin t-t}{t^3}=\frac{1}{2}\cdot2\cdot(-\frac{1}{6})=-\frac{1}{6}.$$

For the last limit to apply the rule of L'Hospital.

$\endgroup$
0
$\begingroup$

Another idea: $$ \lim_{x\to\infty}\left(x\sqrt{x^2-x}-x^2\cos\left(\frac1{\sqrt{x}}\right)\right) = \lim_{x\to\infty}\frac{ \left(x\sqrt{x^2-x}-x^2\cos\left(\frac1{\sqrt{x}}\right)\right)\left(x\sqrt{x^2-x}+x^2\cos\left(\frac1{\sqrt{x}}\right)\right)} {x\sqrt{x^2-x}+x^2\cos\left(\frac1{\sqrt{x}}\right)} = $$ $$ \lim_{x\to\infty}\frac{ x^2(x^2-x)-x^4\cos^2\left(\frac1{\sqrt{x}}\right)}{x\sqrt{x^2-x}+x^2\cos\left(\frac1{\sqrt{x}}\right)} = \lim_{x\to\infty}\frac{ -x^3+x^4\sin^2\left(\frac1{\sqrt{x}}\right)} {x\sqrt{x^2-x}+x^2\cos\left(\frac1{\sqrt{x}}\right)} = $$ $$ \lim_{x\to\infty}\frac{ -x+x^2\sin^2\left(\frac1{\sqrt{x}}\right)} {\sqrt{1-1/x}+\cos\left(\frac1{\sqrt{x}}\right)} = \cdots $$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.